Imperatorin Interferes with LPS Binding to the TLR4 Co-Receptor and Activates the Nrf2 Antioxidative Pathway in RAW264.7 Murine Macrophage Cells - Mei-Hsuen Huang; Yu-Hsien Lin; Ping-Chiang Lyu; Yi-Chung Liu; Yuan-Shiun Chang; Jing-Gung Chung; Wei-Yong Lin; Wen-Tsong Hsieh (MDPI AG, 2021)
Imperatorin (IMP) could downregulate several inflammatory transcription factor signaling pathways. Some studies have pointed out that IMP could interfere with toll-like receptor 4 (TLR4) signaling. This study evaluates how IMP interferes with the TLR4 co-receptors signaling through the protein-ligand docking model, Western blotting, immunofluorescence (IF), and atomic force microscopy (AFM) assays in lipopolysaccharide (LPS) stimulated macrophage-like RAW264.7 cells in vitro. The results of the protein-ligand docking demonstrate that IMP interferes with LPS binding to the LPS-binding protein (LBP), the cluster of differentiation 14 (CD14), and the toll-like receptor 4/myeloid differentiation factor 2 (TLR4/MD-2) co-receptors in LPS-stimulated RAW264.7 cells. Compared with TLR4 antagonist CLI-095 or dexamethasone, IMP could suppress the protein expressions of LBP, CD14, and TLR4/MD-2 in LPS-stimulated cells. Furthermore, the three-dimensional (3D) image assay of the AFM showed IMP could prevent the LPS-induced morphological change in RAW264.7 cells. Additionally, IMP could activate the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway, and it increased the antioxidative protein expression of heme oxygenase-1 (HO-1), superoxidase dismutase (SOD), and catalase (CAT). Our results are the first to reveal that the anti-inflammatory effect of IMP interferes with LPS binding to TLR4 co-receptor signaling and activates the antioxidative Nrf2 signaling pathway.